The interplay between RNA m6A modification and radiation biology of cancerous and non-cancerous tissues: a narrative review - Yajia Cheng; Yue Shang; Shuqin Zhang; Saijun Fan (Cancer Biology & Medicine)
The diverse radiation types in medical treatments and the natural environment elicit complex biological effects on both cancerous and non-cancerous tissues. Radiation therapy (RT) induces oncological responses, from molecular to phenotypic alterations, while simultaneously exerting toxic effects on healthy tissue. N6-methyladenosine (m6A), a prevalent modification on coding and non-coding RNAs, is a key epigenetic mark established by a set of evolutionarily conserved enzymes. The interplay between m6A modification and radiobiology of cancerous and non-cancerous tissues merits in-depth investigation. This review summarizes the roles of m6A in the biological effects induced by ionizing radiation and ultraviolet (UV) radiation. It begins with an overview of m6A modification and its detection methods, followed by a detailed examination of how m6A dynamically regulates the sensitivity of cancerous tissues to RT, the injury response in non-cancerous tissues, and the toxicological effects of UV exposure. Notably, this review underscores the importance of novel regulatory mechanisms of m6A and their potential clinical applications in identifying epigenetically modulated radiation-associated biomarkers for cancer therapy and estimation of radiation dosages. In conclusion, enzyme-mediated m6A-modification triggers alterations in target gene expression by affecting the metabolism of the modified RNAs, thus modulating progression and radiosensitivity in cancerous tissues, as well as radiation effects on normal tissues. Several promising avenues for future research are further discussed. This review highlights the importance of m6A modification in the context of radiation biology. Targeting epi-transcriptomic molecules might potentially provide a novel strategy for enhancing the radiosensitivity of cancerous tissues and mitigating radiation-induced injury to normal tissues.